Compound Bacillus alleviates diarrhea by regulating gut microbes, metabolites, and inflammatory responses in pet cats - Fei Wang; Xiaoying Mei; Qi Wang; Pengwei Zhao; Yuanhao Zhou; Li Tang; Baikui Wang; Shujie Xu; Xiang Li; Qian Jin; Yingping Xiao; Weifen Li (Animal Microbiome, 2023)
Abstract Background Pet cats frequently have diarrhea in their daily life. Bacillus has a protective role that has crucial beneficial functions on intestinal homeostasis. The aim of this research was to investigate the effects of the compound Bacillus on the prevention of diarrhea, microbiota and metabolism in pet cats. A total of 20 pet cats (1–2 years old, 3.91 ± 0.92 kg) were randomly divided into two groups and fed with a basal diet (Control group), or a basal diet supplemented with 3 × 109 CFU/kg compound Bacillus (Probiotics group). The experiment lasted 33 days. Results Results showed that the compound Bacillus significantly reduced the rate of soft stools and diarrhea in pet cats compared with the control group (P < 0.05, n = 10). Meanwhile, compared with the control group, the probiotics group significantly decreased the content of IL-1β and IL-6 and significantly increased IL-10 (P < 0.05, n = 6) in the serum. In addition, feeding probiotics significantly increased the abundance of p_Patescibacter and g_Plectosphaerella, decreased the abundance of p_Firmicutes, p_Gemmatimonadetes, g_Ruminococcaceae_UCG-005, g_Ascochytahe and g_Saccharomyces in the feces of the pet cats (P < 0.05, n = 6). And it also can significantly increase the content of total SCFAs, acetic acid and butyric acid in the feces (P < 0.05, n = 6). The fecal and serum metabolomics analyses revealed that most fecal and serum compounds were involved in metabolism, particularly in chemical structure transformation maps and amino acid metabolism. Also, eugenitol and methyl sulfate were the most significantly increased serum metabolites, and log2FC were 38.73 and 37.12, respectively. Pearson’s correlation analysis showed that changes in serum metabolism and fecal microbiota were closely related to immune factors. There was also a strong correlation between serum metabolites and microbiota composition. Conclusions The results of this research highlight the potential of the compound Bacillus as a dietary supplement to alleviate diarrhea in pet cats.